Effects of preservation method on fruiting body formation and cordycepin production of Cordyceps militaris culture - Natthapong Singpoonga (2020)
© 2019 Elsevier B.V.. All rights reserved. Preservation was investigated of Cordyceps militaris mycelial cultures under eight different methods: freezing at -80°C; chilling at 5°C in 10% (volume per volume; v/v) glycerol; chilling at 5°C on rice grains that had been dried at 35°C, 45°C or 55°C; and three subculturings involving holding at 5°C. The cultivation of the original strain before the preservation tests was used as the control. The viability, purity and stability of the mycelia were tested after 4 mth storage. Fruiting body production and physico-chemical properties, together with the cordycepin production were determined. All preservation methods resulted in high viability and purity of the cultures. However, the stability of the preserved culture was significantly (p < 0.05) different among the preservation methods. Cultures chilled at 5°C on rice grains dried at 35°C, 45°C or 55°C and the three subculturing methods affected the size of the colony diameter (p < 0.05). Freezing at -80°C, chilling at 5°C in 10% (v/v) glycerol or keeping on rice grains dried at 35 or 45°C did not affect the number of fruiting bodies produced, fresh weight, firmness, total soluble solids or color (p > 0.05). Cultures frozen at -80°C, chilled at 5°C in 10% (v/v) glycerol, or kept on rice grains dried at 35°C compared to the control did not show any significant (p > 0.05) differences in cordycepin production, while subculturing negatively affected cordycepin production after 4 mth storage.